Informing America's Policy on Illegal Drugs: What We Don't Know Keeps Hurting Us - National Research Council (U.S.). Committee on Data and Research for Policy on Illegal Drugs; Manski, Charles F.; Pepper, John; Petrie, Carol; National Research Council (U.S.). Committee on Law and Justice; National Research Council (U.S.). Commission on Behavioral and Social Sciences and Education. Committee on National Statistics (National Academies Press, 2001)
How should the war on drugs be fought? Everyone seems to agree that the United States ought to use a combination of several different approaches to combat the destructive effects of illegal drug use. Yet there is a remarkable paucity of data and research information that policy makers require if they are to create a useful, realistic policy package-details about drug use, drug market economics, and perhaps most importantly the impact of drug enforcement activities. Informing America's Policy on Illegal Drugs recommends ways to close these gaps in our understanding-by obtaining the necessary data on drug prices and consumption (quantity in addition to frequency); upgrading federal management of drug statistics; and improving our evaluation of prevention, interdiction, enforcement, and treatment efforts. The committee reviews what we do and do not know about illegal drugs and how data are assembled and used by federal agencies. The book explores the data and research information needed to support strong drug policy analysis, describes the best methods to use, explains how to avoid misleading conclusions, and outlines strategies for increasing access to data. Informing America's Policy on Illegal Drugs also discusses how researchers can incorporate randomization into studies of drug treatment and how state and local agencies can compare alternative approaches to drug enforcement. Charting a course toward a better-informed illegal drugs policy, this book will be important to federal and state policy makers, regulators, researchers, program administrators, enforcement officials, journalists, and advocates concerned about illegal drug use.